FAKTOR-FAKTOR PENDUKUNG PELAKSANAAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA: PERSEPSI GURU SD NEGERI 25 MATTIROWALIE - Sudarto, Sudarto; Sitti Rahmi; Minda Pra Ramadhani (Bajang Institute, 2024)
This research is a descriptive qualitative study which aims to determine the teachers' perceptions of the supporting factors for implementing the Pancasila Student Profile Strengthening Project (PSPSP). The subjects in this research were the homeroom teachers of SD Negeri 25 Mattirowalie, IN totaling of 4 people. The data collection technique used was the interview technique and the data analysis technique used was data reduction, data presentation and drawing conclusions. The research results showed that the supporting factors in implementing PSPSP based on the teacher perceptions were: (1) the existence of the students who were active and enthusiastic in implementing the project, (2) the existence of the great support from the headmaster, (3) the existence of the adequate facilities to implement the PSPSP, (4) there was a great support from the school supervisor, (5) there was a solidarity between the colleagues and teachers, (6) there was an understanding from the parents towards the PSPSP, and (7) there was a support from the community around the school